Strategi Kolaborasi Antar Pelaku Logistik untuk Meningkatkan Kepercayaan Konsumen dalam Industri Halal Global - Wulandari, Mery; Kusuma, Hendri Prima (Jurnal Kesehatan & Disiplin Ilmu, 2025)
The global halal industry is experiencing rapid growth, demanding strict logistics standards to ensure compliance with halal principles. This study explores collaboration strategies between logistics actors in increasing consumer confidence. With a qualitative approach and case studies on several halal logistics companies, this study finds that synergy between stakeholders, mutual certification, and the application of transparency and traceability-based technologies play a key role in strengthening consumer trust. The results of this study provide insight for the halal logistics industry in developing an effective collaboration model.